AL-QUR’AN DAN PEMBANGUNAN LINGKUNGAN BERKELANJUTAN DI INDONESIA: ANALISIS MAQASHID SYARIAH UNTUK PENCAPAIAN SDGs - Slamet Firdaus (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2022)
This article will explore the Islamic worldview on environmental development which is the main problem of the world community today. One that did not receive much attention in this study was the role of religion and all related components in contributing to the realization of sustainable environmental development. These environmental issues are part of the SDGs agenda which requires a new perspective through comparison with the maqasid shariah framework, specifically to analyze the agenda of SDGs 2030 in Indonesia, especially the pillars of environmental development with targets and priorities in realizing it. For this reason, text interpretation and content analysis methods are used to examine sources of religious texts, especially verses of the Qur'an that reveal the relationship between Islam, development, and the environment, as well as road map documents and Indonesia's SDGs 2017-2030 policy. The conclusion of this article emphasizes that the Qur'an as a source of the Islamic law that has a philosophical foundation is operationalized through maqasid shariah as the goals of Islamic law set by Allah to realize goodness for humans through sustainable environmental development and the application of environmental ethics for all human beings. for its sustainability in the future.Keywords: Holy Qur’an; Maqasid Shariah; SDGs; Environmental Ethics; Environmental Sustainability